Inhibition of protein kinase C signaling protects prefrontal cortex dendritic spines and cognition from the effects of chronic stress - Hains, Avis Brennan (National Academy of Sciences, 2009)
The prefrontal cortex r regulates behavior, cognition, and emotion by using working memory. Prefrontal functions are impaired by stress exposure. Acute, stress-induced deficits arise from excessive protein kinase C (PKC) signaling, which diminishes prefrontal neuronal firing. Chronic stress additionally produces architectural changes, reducing dendritic complexity and spine density of cortico-cortical pyramidal neurons, thereby disrupting excitatory working memory networks. In vitro studies have found that sustained PKC activity leads to spine loss from hippocampal-cultured neurons, suggesting that PKC may contribute to spine loss during chronic stress exposure. The present study tested whether inhibition of PKC with chelerythrine before daily stress would protect prefrontal spines and working memory. We found that inhibition of PKC rescued working memory impairments and reversed distal apical dendritic spine loss in layer II/III pyramidal neurons of rat prelimbic cortex. Greater spine density predicted better cognitive performance, the first direct correlation between pyramidal cell structure and working memory abilities. These findings suggest that PKC inhibitors may be neuroprotective in disorders with dysregulated PKC signaling such as bipolar disorder, schizophrenia, post-traumatic stress disorder, and lead poisoning—conditions characterized by impoverished prefrontal structural and functional integrity.